Unexplained Progressive Visual Field Loss in the Presence of Normal Retinotopic Maps - Moutsiana, Christina; Soliman, Radwa; de Wit, Lee; James-Galton, Merle; Sereno, Martin I.; Plant, Gordon T.; Schwarzkopf, D. Samuel (Frontiers in Psychology, 2018)
Lesions of primary visual cortex or its primary inputs typically result in retinotopically localised scotomas. Here we present an individual with unexplained visual field loss and deficits in visual perception in the absence of structural damage to the early visual pathway or lesions in visual cortex. The subject, monocular from an early age, underwent repeated perimetry tests over eight years demonstrating severe anopia of the lower hemifield, and a clockwise progression of the loss through her upper left visual field. Her visual impairment was evident in a number of standardized tests and psychophysics, especially in tasks assessing spatial integration using illusory contours. However, her intellectual ability was intact and her performance in some other tasks assessing colour vision or object detection in scenes was normal. We employed functional magnetic resonance imaging (fMRI), electroretinography and visually evoked potentials. Surprisingly, in contrast to the participant’s severe anopia, we found no evidence of abnormal function of her early visual pathways. Specifically, we performed retinotopic mapping using population receptive field (pRF) analysis to map the functional organization of visual cortex in the anopic participant and three control participants on two occasions three and a half years apart. Despite the behavioural visual field loss, her retinotopic maps and pRF parameters in visual areas V1-V3 were qualitatively normal. Further behavioural experiments confirmed that this discrepancy was not trivially explained by the difference between stimuli used for retinotopic mapping and perimetry. Structural T1 scans were normal at both time points, and volumetric analysis of white and grey matter tissue on the segmented T1 volumes did not reveal any abnormalities or deterioration over time. Our findings suggest that normal functional organization of early visual cortex without evident structural damage to the early visual pathway as disclosed by the techniques employed in this study does not necessarily guarantee conscious perception across the visual field.